Irrigation management in relation to waterlogging and salinity: precise for a research agenda in Pakistan - Kijne, Jacob W. (International Irrigation Management Institute, 1989)
This paper presents an overview of the current state of knowledge on the relations between irrigation management in Pakistan and the incidence of waterlogging and salinity. It is emphasized that management research should focus on the whole system, including surface and ground water resources. The paper also highlights key management questions that need to be addressed such as salt and water balance and water loss from canals, water courses and field channels.